?POLYMETALLIC COMPLEXES Part-XLV. Complexes of Co (II), Ni (II), Cu (II), Zn (II), Cd (II) and Hg (II) with Bis-Bidentate Chelating Diazo Dye Ligands - MAHAPATRA, BIPIN B.; SATYANARAYAN, D.; BElIERA, A.K. (Biological Sciences - PJSIR, 1994)
Bis-bidentate ligands 1-(2-carboxyphenyl-azo)-2,4-dihydroxy-benzene and 4,4’-bis (2,4-dihydroxyphenyl-1-azo- 3,3’ -dimethyl)-diphenyl having ON-NO and 6N.n.NO potential donor atoms respectively form polynulear complexes with some divalent transitional and non-transitional metal ions. The nickel (II) complex with former ligand is found to be square-planar whereas the other cobalt (IT),nickel (IT)and copper (IT)complexes are either octahedral or distorted octahedral. The complexes with zinc (II), cadmium (IT)and mercury (II) are assigned to have tetrahedral stereochem- istry around the metal ions. The characterisation of the complex compounds has been made basing upon analytical, con- ductance, magnetic susceptibility measurement, thermal i.r., electronic spectra, n.m.r and e.s.r spectral data.